A distributed energy-balance melt model of an alpine debris-covered glacier - Fyffe, Catriona; Reid, Tim; Brock, Benjamin; Kirkbride, Martin; Diolaiuti, Guglielmina; Smiraglia, Claudio; Diotri, Fabrizio (Journal of Glaciology, 2014)
Distributed energy-balance melt models have rarely been applied to glaciers with extensive supraglacial debris cover. This paper describes the development of a distributed melt model and its application to the debris-covered Miage glacier, western Italian Alps, over two summer seasons. Sub-debris melt rates are calculated using an existing debris energy-balance model (DEB-Model), and melt rates for clean ice, snow and partially debris-covered ice are calculated using standard energy-balance equations. Simulated sub-debris melt rates compare well to ablation stake observations. Melt rates are highest, and most sensitive to air temperature, on areas of dirty, crevassed ice on the middle glacier. Here melt rates are highly spatially variable because the debris thickness and surface type varies markedly. Melt rates are lowest, and least sensitive to air temperature, beneath the thickest debris on the lower glacier. Debris delays and attenuates the melt signal compared to clean ice, with peak melt occurring later in the day with increasing debris thickness. The continuously debris-covered zone consistently provides ∼30% of total melt throughout the ablation season, with the proportion increasing during cold weather. Sensitivity experiments show that an increase in debris thickness of 0.035 m would offset 1°C of atmospheric warming.